The disabled consumer: Between autonomy, discrimination and administrative justice - Díaz Díaz, María-Pía Guadalupe (2022)
Disabled people in Peru directly participate in contractual consumption relationships to satisfy their desires and needs based on a recognition of their full legal capacity. In this regard, law seeks to ensure their autonomy and access; nevertheless, discrimination appears as an obstacle. This study explores the role of support, reasonable adjustments, and administrative justice in the field of contractual consumption relationships of disabled people. The methodology includes addressing doctrine, legal regulations, and case law on the matter. The conclusion is that support and reasonable adjustments play a fundamental role, along with administrative justice by INDECOPI, in removing obstacles from this contractual scenario to fully include disabled people in society.